Quantitative Analysis of Microcystin-LR in Drinking Water Comparing On-Line Solid Phase Extraction and Direct Injection LC/MS/MS - R. MALARVILI; Y.Y. LOW; A. ZAITON (ASEAN Journal on Science and Technology for Development, 2017)
An efficienmethod for microcystin-LRin drinking water at the sub-ng/l level applying on-line solid phase extraction (SPE) with LC/MS/MS detection and comparing it to direct injection LC/MS/MS is presented. The performance of the method of direct injection did not signifiantly deviate from the SPE approach. However, the direct injection method used less sample volume (100 µl) in shorter analysis time (4 min) and allowed more sample throughput. Conversely, the uncertainty of measurement could be reduced using SPE.